Effect of microwave irradiation and water storage on the viscoelastic properties of denture base and reline acrylic resins - Leao Lombardo, Carlos Eduardo; Canevarolo, Sebastiao Vicente; dos Santos Nunes Reis, Jose Mauricio; Machado, Ana Lucia [UNESP]; Pavarina, Ana Claudia [UNESP]; Giampaolo, Eunice Teresinha; Vergani, Carlos Eduardo [UNESP] (Elsevier B.V., 2012)
This study evaluated the effect of microwave irradiation and water storage on the viscoelastic properties of two denture base resins (Lucitone 550-L and Vipi Wave-VW) and two reline resins (Kooliner-K and Tokuyama Rebase Fast II-TR II). Eight specimens (40 x 10 x 3.3 mm) of each material were evaluated by dynamic mechanical thermal analysis (DMTA) after processing, water storage for 7 days (WS), one (MW1) and 7 cycles of microwave irradiation (MW7). For each specimen, DMTA runs were carried out within different temperature intervals. Values of storage modulus (E') and loss tangent (tan 3) at 37 degrees C were obtained from the first and last runs. From the last run, values of E' at the glass transition temperature (Tg) and maximum tan delta were also recorded. Data were analyzed by a 2-way ANOVA followed by Student-Newman-Keuls test (alpha = 0.05). Measurements of the inside temperature of each specimen during microwave irradiation (650 W/3 min) were conducted using a fiber optic temperature sensor. Six specimens of each material were evaluated. During microwave irradiation, all specimens reached the boiling temperature of water at approximately 130 s. From the first DMTA run, MW1 and WS significantly increased the E' and decreased the tan delta of K at 37 degrees C (P < 0.05). From the last run, the tan 6 of K and TR II was significantly decreased after MW 1 (P < 0.05). MW 7 decreased the tan delta of K (P < 0.05). The E' of L and VW was similar and higher than K and TR II (P < 0.05). At Tg, K produced the lowest E' and its maximum tan,S was increased after MW1 (P < 0.05). The Tg mean values were arranged as: L > VW > TR II > K (P < 0.05). Microwave irradiation and WS did not detrimentally affect the viscoelastic properties of the denture base and reline resins evaluated. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Acrylic resin; Microwave irradiation; Glass transition; DMTA; Viscoelastic